Effects of 2,4,6-trinitrotoluene (TNT) on neurosteroidogenesis in the European eel (Anguilla anguilla; Linnaeus 1758) - DELLA TORRE, CAMILLA; CORSI, ILARIA; FOCARDI, SILVANO ETTORE; ARUKWE A. (Chemistry and Ecology, 2008)
The aim of the present study is to investigate the endocrine disrupting potential of the explosive 2,4,6-trinitrotoluene (TNT) on marine organisms using the European eel (Anguilla anguilla Linnaeus, 1758) as model fish species. Crucial brain steroidogenic parameters such as the estrogen receptors (ERs), P450 aromatase (CYP19), steroidogenic acute regulatory (StAR) protein and P450-mediated cholesterol side-chain cleavage (P450scc) enzyme were selected as potential biomarkers for the assessment of TNT endocrine disrupting potential. Juvenile European eels were exposed for 6 and 24h to 0.5, 1 and 2.5mg/l nominal concentration of TNT dissolved in dimethyl sulfoxide (DMSO). ER alpha CYP19, StAR protein and P450scc genes expression were quantified using real-time PCR. Exposure to TNT altered the expression of ER gene at the lowest TNT concentration after 6h of exposure, while after 24h gene expression levels increased respect to controls only in eels at the maximum TNT dose (2.5mg/l). A significant increase of CYP19 gene expression occurred after 6 h in all eels exposed to TNT compared to controls. On the opposite at 24h, CYP19 expression seems reduced in eels exposed to 0.5 and 1mg TNT/l compared to 6h, while no changes were observed at the highest dose (2.5mg/l). Both StAR and P450scc gene expression were decreased at 6h in eels exposed to 0.5 and 1mg TNT/l, while at 2.5mg TNT/l, the gene expression levels were restored to background level. No further modulation was evident after 24h for both genes. The overall results indicate the ability of TNT to affect neurosteroidogenic pathways.